If it's not what You are looking for type in the equation solver your own equation and let us solve it.
53+39=4+7x
We move all terms to the left:
53+39-(4+7x)=0
We add all the numbers together, and all the variables
-(7x+4)+53+39=0
We add all the numbers together, and all the variables
-(7x+4)+92=0
We get rid of parentheses
-7x-4+92=0
We add all the numbers together, and all the variables
-7x+88=0
We move all terms containing x to the left, all other terms to the right
-7x=-88
x=-88/-7
x=12+4/7
| g–4+ –2=–6 | | 8x=61 | | 23-2x=-5+4(x+4) | | 3x–49=32 | | 5+(5+3x)=35 | | 9/5x-1/6=-1 | | 2xx-7=-23 | | 45=52+x | | 2x-2/6=-6 | | –8−6r=–7r | | 7n+7=8n | | 3x12=x4 | | 100+8x=800 | | 2=x-6*x | | 25-4n=-5(n-4) | | 2=x-6•x | | 10+27x−9x=10+18x | | 84=5x+3x+4 | | x–28=34 | | 3x-7(x+5)=-35 | | 2m-44=76-8 | | 5x-3x+7=3x+4x-3 | | 29=w/2+12 | | 60+80=x+50 | | 3x=2/5=4 | | 8x-30=26 | | w/3+15=37 | | 16=35+2t | | V=1/2X2*h | | (3x+20)=(4x-10) | | 2x-x3x-x=-6 | | X*x=30.25 |